Can Foreign Sales, Sales Growth, and Good Supervisions Affect Transfer Pricing Aggressiveness? - Bahrun, Muhammad Fadly; Sustiyo, Joko (Studi Akuntansi dan Keuangan Indonesia, 2023)
This study examines the effects of foreign sales, sales growth, women on board, and audit quality on transfer pricing. The relationship between these variables is explained by agency theory. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2012 until 2019. The method used to determine the number of samples is purposive sampling. Panel data analysis and random effect model estimators have been applied to achieve the object of this study. The results of this study indicate that: (1) foreign sales do not affect transfer pricing; (2) sales growth has a negative and significant impact on transfer pricing; (3) women on board has a positive and significant impact on transfer pricing; (4) audit quality does not affect transfer pricing.